ESG평점과 한국 기업의 생산성 - 김정욱; Jungwook Kim; 이종화; Jong Hwa Lee (자원·환경경제연구, 2025)
본 연구는 최근에 많은 관심을 갖는 한국 금융시장에 상장된 기업들의 Environmental, Social, and Governance (ESG) 평점이 총요소생산성과 관계가 있는지 모색한다. 내생성을 극복하기 위해 도구변수방법과 지연회귀분석(Lagged-term regression)을 활용해서 환경, 사회, 지배구조의 질을 대변하는 종합지수는 기업의 생산성을 설명하기엔 부족하다는 결과를 보인다. 그러나 ESG 점수는 노동 생산성과 긍정적으로 관련되어 있다는 결과를 도출한다. 노동 시장이 ESG 성과와 기업 생산성이 연결된 경로임을 주장하며, 기업이 이 경로를 활용할 수 있는지는 재정 제약에 달려 있다고 분석한다. This study tests the relationship between environmental, social, and governance (ESG) scores and firm productivity in South Korea. We employ a lagged-term regression analysis and instrumental variable approach to find that the composite score of ESG is inadequate in explaining total factor productivity (TFP). This finding is due to the mixed direction that each E, S, and G component has on TFP. The governance component consistently impacts firm productivity while Environment and Social components do not. Additionally, labor productivity is positively linked with ESG scores. We argue that the labor market is the channel through which the ESG performance and firm productivity are linked and whether firms can exploit this channel depends on financial restrictions.